Metabolic Disorders and Inflammatory Bowel Diseases - Hye Kyung Hyun; Jae Hee Cheon (Gut and Liver)
Inflammatory bowel disease (IBD) is characterized by chronic immune-mediated intestinal inflammation, presenting with a spectrum of metabolic disorders as well as intestinal and extraintestinal manifestations. Lifestyle factors, genetic predisposition, immune dysfunction, and gut bacteria composition contribute to the development of IBD. Several comorbidities, including cardiovascular diseases, thrombosis, and metabolic disorders, have been associated with IBD. Therefore, metabolic disorders, including nonalcoholic fatty liver disease, type 2 diabetes mellitus, and obesity have become the focus of attention in patients with IBD. Identifying and managing these conditions can significantly influence patient outcomes and enhance overall management. Therefore, this review aimed to elucidate the current understanding of relevant and emerging metabolic comorbidities and extraintestinal manifestations associated with IBD and their clinical significance.